Aggression Assessment and Plasma Serotonin Level amongst Pakistani Youngsters - Sumaira Riffat, Sahar Zahid, Mushtaq Hussain, Raza Ur Rehman, Masood Anwar Qureshi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Aggressive behavior is a multifaceted construct involving various physiological modulators and genetic factors with a variable frequency in different populations. Of multiple genetic factors, serotonin is known to have profound role with disagreement exists in relation to its expressional alignment with the intensity of aggression. The existing study is designed to develop alignment of the psychological scale of aggression with the plasma serotonin levels. Methodology: Buss Perry Aggression Questionnaires (BP-AQs) were distributed among male and female students of different universities of Karachi. Among those, 2000 properly filled questionnaires were selected to be scrutinized and scored which led to selection of 80 students each of score lower than 60 (least aggressive individuals) or higher than 100 (most aggressive individuals). Plasma serotonin levels of the 160 individuals were then measured by ELISA. Results: Cumulatively, males tend to have higher BP-AQ score than females (79.14+16.22 vs. 75.28+16.97) and also in physical aggression (23.81+6.44 vs. 21.05+6.17) statistically significant difference of p=0.0011 and p<0.0001, respectively. All scores of different forms of aggression were found positively correlated with each other and with strong statistical significance. Level of serotonin was found significantly higher (p=0.0004) in females (244ng/ml) compared to males (70.39ng/ml). Plasma serotonin levels were negatively correlated with BP-AQ scores especially in females (p=0.0222) and in whole of the assessed subjects (p=0.0069). Practical implication: In order to facilitate a better understanding of aggressive behaviour, this study helps to align a physiological biomarker with psychological tools. Additionally, serotonin can be used as a biomarker to comprehend the physiological underpinnings of aggression, and future studies can be planned that use serotonin or its receptors in relation to aggressive behaviour. And it will positively impact the mental health of any society. Conclusion: The findings in total suggest male holds more aggressive behavior especially physical aggression compared to females. Additionally, the aggression in female is more profoundly associated with the low plasma serotonin level. Keywords: Aggression, Behavior, Hostility, Adolescents, Neurotransmitters, Serotonin,